Recent advances in detection techniques and chemometric methods for identifying adulterants in milk and dairy products - Norliza Julmohammad; Emeline Tan; Muhammad Rahimi Yusop; Salma Samidin (Elsevier, 2025)
Milk adulteration poses a significant threat to food safety, driven by increasing global demand for milk and dairy products, particularly in developing countries. Supply limitations, compounded by challenges like pandemics and livestock diseases such as mastitis, often lead to unethical practices that compromise product quality and consumer health. Adulterants, including preservatives, non-milk fats, thickening agents, nitrogen-based compounds, and surfactants, are intentionally added to mimic natural properties or enhance the solid-not-fat (SNF) content of milk. Advanced detection techniques, such as spectroscopy, chromatography, biosensors (protein and DNA-based), and electromigration methods like SDS-PAGE, have emerged as critical tools for identifying these adulterants. Innovative approaches, including electrical sensors like electronic noses and tongues, further enhance detection accuracy. This study highlights recent advancements in instrumental techniques alongside the pivotal role of chemometric methods in analyzing complex datasets, improving precision, and ensuring reliable detection, offering insights into current progress, challenges, and opportunities in safeguarding milk integrity.